Dampak Penggunaan Aditif Distilat Asam Lemak Minyak Sawit pada Organoleptik Beras Analog - I Made Bagus Lingga Puspayana; Faleh Setia Budi (Institut Pertanian Bogor, 2019)
Commercial rice analogues have not been able to reduce the level of rice consumption because the price is relatively expensive. One of the contributing factors is the use of glycerol monostearate (GMS) as a lubricant agent in the extrusion process. Palm fatty acid distillate (PFAD) is a by-product of crude palm oil refining process with distillation technology which has the potency to be used as a lubricating agent in the extrusion process. PFAD prices which is cheaper than GMS is expected to be able to reduce the price of commercial rice analogues. The use of PFAD as a lubricating agent in the extrusion process of rice analogous manufacturing was predicted not to reduce the organoleptic properties of rice analogous significantly. This research aimed to access the influence of PFAD on the decrease of organoleptic properties of analog rice. Rice analogues were made from a mixture of corn flour, sago starch, and PFAD with 4 formulations i.e., 2, 3, 4, and 5%. Water was added until the final moisture content of the dough reached 40%. Extruder was operated at screw speed of 150 rpm and temperature 90oC. The organoleptic properties of produced rice analogous was analyzed. The result showed that the use of PFAD in extrusion process for rice analogous manufacturing decreased the organoleptic properties of cooked rice analogous (aroma, taste, texture, and overall) but it did not affect the attribute of color.